E-Groups and E-Rings - Krylov, P. A.; Tuganbaev, A. A.; Tsarev, A. V. (Journal of mathematical sciences (New York, N.Y.), 2021)
An associative ring R is called an E-ring if the canonical homomorphism R ≅ E( R + ) is an isomorphism. Additive groups of E -rings are called E-groups . In other words, an Abelian group A is an E -group if and only if A ≅ End A and the endomorphism ring E( A ) is commutative. In this paper, we give a survey of the main results on E -groups and E -rings and also consider some of their generalizations: ε -closed groups, T -rings, A -rings, the groups admitting only commutative multiplications, etc.